Application of simply and conveniently recycled IL-coated MT composite material in treatment of antiviral drug pollutants in wastewater

Through the application of modified ionic liquid and montmorillonite composite materials, the problem of removing antiviral drug pollutants in sewage is solved, efficient adsorption and catalytic degradation are achieved, the removal rate is significantly improved, and the advantages of simple recycling are provided.

CN119633743APending Publication Date: 2025-03-18TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311191460.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing sewage treatment technologies are difficult to effectively remove antiviral drug contaminants, causing them to remain in water, posing a threat to ecosystems and human health.

Method used

The modified ionic liquid (IL) and montmorillonite (MT) composite materials are used to impart catalytic performance by adjusting the structure of IL, and the porosity and structural design of MT are used to enhance its adsorption and catalytic degradation of antiviral drug contaminants.

Benefits of technology

The removal rate of antiviral drug contaminants is significantly improved, and the effect of efficiently removing contaminants without the need for adding oxidants or additional solvents is achieved, and the simple recycling of materials is achieved through external stimulation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to application of an ionic liquid and montmorillonite composite material with external stimuli response performance to removal of antiviral drug pollutants in wastewater. The composite material disclosed by the invention has adsorption and catalytic performances, the structure of the ionic liquid is adjusted to endow the composite material with high catalytic selectivity, and the structure of the montmorillonite is adjusted to endow the composite material with high adsorption selectivity, so that the purposes of in-situ adsorption and catalytic degradation of antiviral drug pollutants are achieved. After the reaction is finished, the in-situ separation of the material can be realized through an external stimulation method for subsequent recycling, and the removal effect on the antiviral drug pollutants can reach 82%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent and catalyst material application, and relates to the application of an ionic liquid-montmorillonite composite material in treating antiviral drug pollutants in wastewater. Background Art

[0002] Wastewater treatment plants cannot effectively remove residual drugs, including antiviral drugs, from human excreta. The extensive use of antiviral drugs leads to large amounts of excretion in urban wastewater, which can then be released into the environment, causing adverse effects on the ecosystem. Antiviral drug residues are easily discharged into water bodies due to their poor biodegradability, causing chronic toxicity to aquatic organisms in natural water bodies, and further causing harm to the human body through the means of bioaccumulation.

[0003] Adsorption and degradation are two commonly used methods for removing pollutants from water. Adsorption is an effective physical method. Due to its simplicity, high efficiency, economy and environmental protection, it has been widely used in the removal of organic pollutants in various matrices. The selection of adsorbents with excellent adsorption capacity and regeneration ability is crucial for the adsorption effect. Porous materials have high specific surface area and limited pore space, and have great adsorbent potential. Montmorillonite (MT) is a good water remediation material. The modification of surfactants changes the hydrophilicity of the montmorillonite surface into hydrophobicity to form organic montmorillonite, thereby achieving the purpose of adsorbing organic pollutants. The degradation method often uses oxidants and high-energy consumption Fenton process, etc., which increases costs. Catalytic hydrolysis of antiviral drug pollutants in water has opened up a new idea. In this process, no additional solvents such as oxidants need to be added. The degradation of antiviral drug pollutants can be achieved by adding catalysts. Ionic liquid (IL) is a highly efficient mass separation agent with advantages such as low melting point, similar or greater density than water, high viscosity, low vapor pressure, and high surface tension. The new generation of IL has high biocompatibility and biodegradability, and has excellent miscibility with a variety of other substances. Its physicochemical properties can be adjusted through specific anion and cation combinations and different structures can be designed. IL has a wide range of applications in many fields. It is a good adsorbent modifier and catalyst, and is also considered to be a good substitute for modern surfactants. Using IL to modify MT and designing an easily recyclable IL@MT composite material, which has both adsorption and catalytic degradation functions for the removal of antiviral drug pollutants in water, can greatly improve its removal effect. Summary of the invention

[0004] The object of the present invention is to provide an IL@MT composite material which can be used to simultaneously realize adsorption and degradation of antiviral drug pollutants in water. The composite material is prepared by stirring and mixing a modified IL and a modified MT material according to a certain molar ratio. The simultaneous adsorption and catalytic degradation functions are realized by adjusting the structure of the IL to endow it with catalytic properties and utilizing the porosity and structural designability of the MT to enhance its adsorption selection function.

[0005] The modified IL-grafted MT composite material proposed in the present invention is as follows:

[0006] 1) First, add 1-10g MT into the modifier solution, seal it with plastic wrap and poke holes with a needle to allow the steam to condense and reflux;

[0007] 2) Oscillate in a constant temperature water bath at 50-150°C and an oscillation rate of 100-200 r / min for 1-12 hours. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind it through a 100-mesh sieve to obtain the modified MT for use.

[0008] 3) Dissolve 1-100g of biomass in the modifier solution and stir magnetically at room temperature for 1-24h. Then add the modified MT and stir at room temperature for 1-12h. Centrifuge the obtained mixture several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a culture dish, dry it at 60-80℃ to constant weight, grind and sieve it for use, and obtain the biomass modified MT intercalation complex: MT / Bio;

[0009] 4) Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or a pyridine derivative or a quaternary ammonium salt derivative, react at a temperature range of 50-120° C. for 1-12 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, thereby obtaining compound 1;

[0010] 5) Add compound 1 into water and dissolve it. Add a heteropolyacid aqueous solution containing an equimolar amount of compound 1 dropwise during stirring. After the addition is complete, raise the temperature to 60-100° C. at a heating rate of 1-10° C. per minute and react for 1-10 hours. Finally, filter out the solid precipitate and send it to a vacuum drying oven for drying to obtain compound 2;

[0011] 6) Dissolve compound 2 in deionized water at 50-120° C., then mix it with metal chloride and add it, react at 90-120° C. for 1-6 hours to obtain an ionic liquid with temperature control function.

[0012] 7) Soak MT-bio in deionized water for 24 hours and then centrifuge. Take 1-10g MT and mix it with NaCl solution, stir for 24-48 hours, dialyze in deionized water until chlorine-free, and then dry at 80℃-100℃. Then pass the prepared material through a 53mm sieve and add IL that exceeds the cation exchange capacity of MT to finally form a temperature-controlled Mt / bio-IL composite material.

[0013] The MT in step 1) includes sodium montmorillonite, calcium montmorillonite, potassium montmorillonite, magnesium montmorillonite, etc.;

[0014] The modified solution in step 1) is an acidic aqueous solution such as hydrochloric acid and sulfuric acid, an alkaline aqueous solution such as ammonia water, and an oxidizing modifier such as hydrogen peroxide and ozone;

[0015] The mass ratio of MT to biomass in steps 1) and 3) is 1:1-1:10;

[0016] In the step 4), the volume ratio of 1,3-propane sultone to toluene is 0.1-1:1; the amount of N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative added is 0.013 mol-0.065 mol.

[0017] In the step 6), the metal chloride is specifically AlCl3 or CrCl3; the molar ratio of the metal chloride to the compound 2 is 1:0.1-1.

[0018] In the step 7), the mass ratio of MT to NaCl solution is 1:1-1:20;

[0019] In the step 7), the molar ratio of MT to IL is 1:1-1:10.

[0020] The method for using the easily recyclable IL@MT composite material prepared by the present invention in treating antiviral drugs in wastewater is as follows:

[0021] The prepared material is added to wastewater containing antiviral drugs, and then the system is placed in a water bath oscillator and oscillated at a rate of 100r / min-500r / min to allow the pollutants to be fully adsorbed by the composite material. The system is then placed at 60℃-120℃ for 1-24h, and the supernatant is taken for content determination after the reaction. The prepared material can be recovered by external stimulation method.

[0022] The antiviral drug pollutants include anti-HIV, anti-hepatitis, anti-influenza and anti-herpes virus.

[0023] The principle of the present invention is to utilize the porosity of the prepared material to adsorb the drug onto the surface of the material through hydrogen bond interaction, electrostatic effect, etc., and then utilize the catalytic properties of the prepared material to highly selectively degrade the drug to achieve the purpose of efficient removal.

[0024] The beneficial effects of the present invention are as follows: (1) The external stimulus responsiveness of the material solves the problem of difficult recovery of the material in homogeneous reactions and poor mass transfer in heterogeneous reactions; (2) It provides a new approach for the value-added utilization of ionic liquids and montmorillonite materials; (3) The combined use of ionic liquids and montmorillonite can simultaneously achieve the adsorption and catalytic degradation of antiviral drugs, significantly improving the removal rate of antiviral drugs in wastewater. DETAILED DESCRIPTION

[0025] Example 1

[0026] First, 5g of MT was added to the modifier solution, sealed with plastic wrap and pierced with a needle to condense and reflux the steam. Then, it was shaken for 8h in a constant temperature water bath at 60℃ and an oscillation rate of 150r / min. After the reaction, the supernatant was removed by centrifugation, the precipitate was washed with deionized water and collected in a petri dish, and the product was taken out after drying. The modified MT was obtained by grinding through a 100-mesh sieve for standby use. 20g of biomass was dissolved in the modifier solution and magnetically stirred at room temperature for 12h. Then the modified MT was added and stirred at room temperature for 10h. The obtained mixed solution was centrifuged several times and the precipitate was washed with deionized water. The supernatant was discarded and the precipitate was transferred to a petri dish, dried at 80℃ to constant weight, ground and sieved for standby use, and the biomass-modified MT intercalation complex was obtained: MT / Bio. Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative, react at a temperature range of 100°C for 8 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, and then obtain compound 1; add compound 1 to water to dissolve it, and drop a heteropolyacid aqueous solution containing an equimolar amount of compound 1 during stirring. After the dropwise addition is completed, the temperature is raised to 80°C at a heating rate of 1-10°C per minute, and react for 10 hours. Finally, the solid precipitate is filtered out and sent to a vacuum drying oven for drying to obtain compound 2; compound 2 is dissolved in deionized water at a temperature of 120°C, and then mixed with metal chloride and added, and reacted at 90°C for 5 hours to obtain an ionic liquid with temperature control function. MT-bio is soaked in deionized water for 24 hours and then centrifuged. Take 5g of MT and mix it with NaCl solution, stir for 24 hours, dialyze in deionized water until there is no chlorine, and then dry it at 80°C. The prepared material was then passed through a 53 mm sieve and 2.5 g IL was added to finally form a temperature-controlled and biomass-modified IL@MT composite material.

[0027] 10 mg of functionalized IL@MT composite material was weighed and added to 20 ml of 20 mg / L antiviral drug solution. The reaction system was then placed in a constant temperature shaker at 30 ° C and 190 rpm to fully promote the adsorption of antiviral drugs. The system was placed at 100 ° C for degradation reaction for 10 hours. All experiments were carried out under light-proof conditions. It can be observed that the system is in a homogeneous state at the reaction temperature. When the reaction is completed and the temperature approaches room temperature, the system is separated from the solid and liquid, and the composite material can be separated from the system. 0.1M HCl and 0.1M NaOH were used to adjust the system pH to 7. After the reaction, 1 ml of the system supernatant was filtered through a 0.22μm PTFE filter head and the removal rate measured by high performance liquid chromatography was 57%.

[0028] Example 2

[0029] First, 20g MT was added to the modifier solution, sealed with plastic wrap and pierced with a needle to condense the steam and reflux. Then it was shaken for 8h in a constant temperature water bath at 60℃ and an oscillation rate of 150r / min. After the reaction, the supernatant was removed by centrifugation, the precipitate was washed with deionized water and collected in a petri dish, and the product was taken out after drying. The modified MT was obtained by grinding through a 100-mesh sieve for standby use. 25g biomass was dissolved in the modifier solution and magnetically stirred at room temperature for 12h. Then the modified MT was added and stirred at room temperature for 10h. The obtained mixed solution was centrifuged several times and the precipitate was washed with deionized water. The supernatant was discarded and the precipitate was transferred to a petri dish, dried at 80℃ to constant weight, ground and sieved for standby use, and the biomass-modified MT intercalation complex was obtained: MT / Bio. Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative, react at a temperature range of 100°C for 8 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, and then obtain compound 1; add compound 1 to water to dissolve it, and drop a heteropolyacid aqueous solution containing an equimolar amount of compound 1 during stirring. After the dropwise addition is completed, the temperature is raised to 80°C at a heating rate of 1-10°C per minute, and react for 10 hours. Finally, the solid precipitate is filtered out and sent to a vacuum drying oven for drying to obtain compound 2; compound 2 is dissolved in deionized water at a temperature of 120°C, and then mixed with metal chloride and added, and reacted at 90°C for 5 hours to obtain an ionic liquid with temperature control function. MT-bio is soaked in deionized water for 24 hours and then centrifuged. Take 10g MT and mix it with NaCl solution, stir for 24 hours, dialyze in deionized water until there is no chlorine, and then dry it at 80°C. The prepared material was then passed through a 53 mm sieve and 15 g of IL was added to finally form a temperature-controlled and biomass-modified IL@MT composite material.

[0030] Weigh 50 mg of functionalized IL@MF composite material and add it to 30 ml, 50 mg / L antiviral drug solution. Then, the reaction system was placed in a constant temperature shaker at 30 ° C and 190 rpm to fully promote the adsorption of antiviral drugs. Then, the system was placed at 80 ° C for degradation reaction for 8 hours. All experiments were carried out under light-proof conditions. After the reaction, the composite material can be separated from the system by changing the temperature. 0.1M HCl and 0.1M NaOH were used to adjust the system pH to 7. After the reaction, 1 ml of the system supernatant was filtered through a 0.22μm PTFE filter head and the removal rate measured by high performance liquid chromatography was 82%.

[0031] Example 3

[0032] First, add 20g MT to the modifier solution, seal it with plastic wrap and pierce it with a needle to condense the steam and reflux. Then oscillate it in a constant temperature water bath at 60℃ and an oscillation rate of 150r / min for 8h. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind it through a 100-mesh sieve to obtain the modified MT for use. Dissolve 20g biomass in the modifier solution and stir it magnetically at room temperature for 12h. Then add the modified MT and stir it at room temperature for 10h. Centrifuge the obtained mixture several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a petri dish, dry it at 80℃ to constant weight, grind and sieve it for use, and obtain the biomass-modified MT intercalation complex: MT / Bio. Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative, react at a temperature range of 100°C for 8 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, and then obtain compound 1; add compound 1 to water to dissolve it, and drop a heteropolyacid aqueous solution containing an equimolar amount of compound 1 during stirring. After the dropwise addition is completed, the temperature is raised to 80°C at a heating rate of 1-10°C per minute, and react for 10 hours. Finally, the solid precipitate is filtered out and sent to a vacuum drying oven for drying to obtain compound 2; compound 2 is dissolved in deionized water at a temperature of 120°C, and then mixed with metal chloride and added, and reacted at 90°C for 5 hours to obtain an ionic liquid with temperature control function. MT-bio is soaked in deionized water for 24 hours and then centrifuged. Take 10g MT and mix it with NaCl solution, stir for 24 hours, dialyze in deionized water until there is no chlorine, and then dry it at 80°C. The prepared material was then passed through a 53 mm sieve and 30 g of IL was added to finally form a temperature-controlled and biomass-modified IL@MT composite material.

[0033] 100 mg of functionalized IL@MT composite material was weighed and added to 50 ml of 60 mg / L antiviral drug solution. The reaction system was then placed in a constant temperature shaker at 30 ° C and 190 rpm to fully promote the adsorption of antiviral drugs. The system was placed at 60 ° C for degradation reaction for 6 hours. All experiments were carried out under light-proof conditions. After the reaction, the composite material can be separated from the system by changing the temperature. 0.1M HCl and 0.1M NaOH were used to adjust the system pH to 7. After the reaction, 1 ml of the system supernatant was filtered through a 0.22μm PTFE filter head and the removal rate measured by high performance liquid chromatography was 56%.

[0034] Subsequently, an experiment on the removal of antiviral pollutants in actual wastewater was conducted: first, 100 ml of Haihe water was taken and added to 50 mg / L of antiviral pollutants, the system was stirred evenly, and 50 mg of IL@MT composite material was added. The system was then placed in an air bath oscillator at a constant temperature of 30°C and a speed of 190 rpm. After oscillation for 12 hours, the supernatant of the reaction system was taken for content analysis.

[0035] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to achieve the final preparation technology. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention. Matters not covered in the present invention belong to the known technology.

Claims

1. A modified IL-grafted MT composite material proposed in the present invention is as follows: 1) First, add 1-10g MT into the modifier solution, seal it with plastic wrap and poke holes with a needle to allow the steam to condense and reflux; 2) Oscillate in a constant temperature water bath at 50-150°C and an oscillation rate of 100-200 r / min for 1-12 hours. After the reaction is completed, centrifuge to remove the supernatant, wash the precipitate with deionized water and collect it in a petri dish, and take out the product after drying. Grind it through a 100-mesh sieve to obtain the modified MT for use. 3) Dissolve 1-100g of biomass in the modifier solution and stir magnetically at room temperature for 1-24h. Then add the modified montmorillonite and stir at room temperature for 1-12h. Centrifuge the obtained mixture several times and wash the precipitate with deionized water, discard the supernatant and transfer the precipitate to a culture dish, dry it at 60-80℃ to constant weight, grind and sieve it for later use, and obtain the biomass modified MT intercalation complex: MT / Bio; 4) Weigh 1,3-propane sultone and add it to a container, then add toluene to dissolve it, then add N-methylimidazole or a pyridine derivative or a quaternary ammonium salt derivative, react at a temperature range of 50-120° C. for 1-12 hours, wash the solid product obtained after the reaction with ethyl acetate, and send it to a vacuum drying oven for drying, thereby obtaining compound 1; 5) Add compound 1 into water and dissolve it. Add a heteropolyacid aqueous solution containing an equimolar amount of compound 1 dropwise during stirring. After the addition is complete, raise the temperature to 60-100° C. at a heating rate of 1-10° C. per minute and react for 1-10 hours. Finally, filter out the solid precipitate and send it to a vacuum drying oven for drying to obtain compound 2; 6) Dissolve compound 2 in deionized water at 50-120° C., then mix it with metal chloride and add it, react at 90-120° C. for 1-6 hours to obtain an ionic liquid with temperature control function. 7) Soak MT-bio in deionized water for 24 hours and then centrifuge. Take 1-10g of montmorillonite and mix it with NaCl solution, stir it for 24-48 hours, dialyze it in deionized water until it is chlorine-free, and then dry it at 80℃-100℃. Then, pass the prepared material through a 53mm sieve and add IL that exceeds the cation exchange capacity of MT to finally form a temperature-controlled Mt / bio-IL composite material.

2. The MT in step 1) includes sodium montmorillonite, calcium montmorillonite, potassium montmorillonite, magnesium montmorillonite, etc., and the modified solution is an acidic aqueous solution such as hydrochloric acid and sulfuric acid, an alkaline aqueous solution such as ammonia water, and an oxidizing modifier such as hydrogen peroxide and ozone.

3. In the steps 1) and 3), the mass ratio of MT to biomass is 1:1-1:

10.

4. In the step 4), the volume ratio of 1,3-propane sultone to toluene is 0.1-1:1; the amount of N-methylimidazole or pyridine derivative or quaternary ammonium salt derivative added is 0.013 mol-0.065 mol.

5. In the step 6), the metal chloride is specifically AlCl3 or CrCl3; the molar ratio of the metal chloride to the compound 2 is 1:0.1-1.

6. In step 7), the mass ratio of MT to NaCl solution is 1:1-1:20, and the molar ratio of MT to IL is 1:1-1:

10.

7. A method for using the easily recyclable IL@MT composite material prepared by the present invention to treat antiviral drugs in wastewater is as follows: The prepared material is added to wastewater containing antiviral drugs, and then the system is placed in a water bath oscillator and oscillated at a rate of 100r / min-500r / min to allow the pollutants to be fully adsorbed by the composite material. The system is then placed at 60℃-120℃ for 1-24h, and the supernatant is taken for content determination after the reaction. The prepared material can be recovered by external stimulation method.

8. The antiviral drug pollutants described are anti-HIV, anti-hepatitis, anti-influenza and anti-herpes virus drugs, etc.